Diseño plataforma estratégica para la empresa Labrada Consultoría en la Ciudad de Hermosillo, Sonora, México (2016)
This project refers to the design of the strategic platform of the consulting Labrada Company, located in Hermosillo, Sonora, Mexico; In order to structure and define the internal processes and its focus. Besides, to set out objectives and formulate strategies that allow the improvement of operation and reach goals, generating continue growth of the organization to be consolidated in the market. It should be noted that this process has been carry out in order to solve the problems that currently the organization presents. It is important to highlight that for the execution of the objectives and development of results, some management models such as porter's five forces, analysis P.E.S.T and FODA matrix , among others were taken into account and seen across the carreer and were a great support to achieve them.